Evidence for low-power radio jet-ISM interaction at 10 pc in the dwarf AGN host NGC 4395 - Nandi, Payel; Stalin, C. S.; Saikia, Dhruba J.; Riffel, Rogemar A.; Manna, Arijit; Pal, Sabyasachi; Dors, Oli L.; Wylezalek, Dominika; Paliya, Vaidehi S.; Saikia, Payaswini; Dabhade, Pratik; Kissler-Patig, Markus; et al. (The astrophysical journal, 2023)
Black-hole-driven outflows in galaxies hosting active galactic nuclei (AGN) may interact with their interstellar medium (ISM) affecting star formation (SF). Such feedback processes, reminiscent of those seen in massive galaxies, have been reported recently in some dwarf galaxies. However, such studies have usually been on kiloparsec and larger scales and our knowledge of the smallest spatial scales to which these feedback processes can operate is unclear. Here we demonstrate radio jet−ISM interaction on the scale of an asymmetric triple radio structure of ∼10 pc size in NGC 4395. This triple radio structure is seen in the 15 GHz continuum image and the two asymmetric jet-like structures are situated on either side of the radio core that coincides with the optical Gaia position. The high-resolution radio image and the extended [O iii]λ5007 emission, indicative of an outflow, are spatially coincident and are consistent with the interpretation of a low-power radio jet interacting with the ISM. Modelling of the spectral lines using MAPPINGS, and estimation of temperature using optical integral field spectroscopic data suggest shock ionization of the gas. The continuum emission at 237 GHz, though weak, was found to spatially coincide with the AGN. However, the CO(2−1) line emission was found to be displaced by around 20 pc northward of the AGN core. The spatial coincidence of molecular H2 λ2.4085 along the jet direction, the morphology of ionized [O iii]λ5007, and displacement of the CO(2−1) emission argues for conditions less favorable for SF in the central ∼10 pc region.